Policies for sustainable land management in the highlands of Ethiopia: summary of papers and proceedings of a seminar held at the International Livestock Research Institute, Addis Ababa, Ethiopia, 22-23 May 2000. - Jabbar, Mohammad Abdul; Pender, John L.; Ehui, Simeon (International Livestock Research Institute, 2000)
The objectives of this workshop were to familiarize key policy makers and other stakeholders in Ethiopia with the objectives and activities of the project; review the progress and findings of the project so far; and consider key policy issues affecting the prospects for sustainable land management in the highlands of Ethiopia.